2019
DOI: 10.1021/acsomega.9b01210
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Photon Upconversion Dye-Sensitized Solar Cell by Co-adsorption with Derivative of Pt–Porphyrin and Anthracene on Mesoporous TiO2

Abstract: Photon upconversion via triplet–triplet annihilation (TTA-UC) is a process that converts two lower-energy photons to a higher-energy photon, which is expected to increase the maximum solar cell efficiency beyond the Shockley–Queisser limit. To incorporate TTA-UC into a dye-sensitized solar cell (DSSC), we used a co-adsorption approach, in which both a TTA-UC donor with an alkyl carboxylic acid chain and a TTA-UC acceptor dye were adsorbed onto mesoporous TiO 2 . Incident photon-to-curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…In order to solve the triplet energy migration and sensitizer solubility issue, a co-adsorption approach was introduced (Figure 8b). [199] In this approach, the sensitizer and annihilator are co-adsorbed on the surface of electrode with close proximity, which improved the TET and TTA efficiency thanks to the short distance between upconversion chromophores. An FoM of 0.036 mA cm −2 sun −2 has been achieved in a TTA upconversion [193] Copyright 2016, American Chemical Society.…”
Section: Solid-state Tta Upconversion Integrated Photovoltaicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to solve the triplet energy migration and sensitizer solubility issue, a co-adsorption approach was introduced (Figure 8b). [199] In this approach, the sensitizer and annihilator are co-adsorbed on the surface of electrode with close proximity, which improved the TET and TTA efficiency thanks to the short distance between upconversion chromophores. An FoM of 0.036 mA cm −2 sun −2 has been achieved in a TTA upconversion [193] Copyright 2016, American Chemical Society.…”
Section: Solid-state Tta Upconversion Integrated Photovoltaicsmentioning
confidence: 99%
“…integrated DSSC by co-adsorbing Pt(II)−porphyrin dye and diphenylanthracene on mesoporous TiO 2 . [199] Nevertheless, this approach has the disadvantage of the relatively low light harvesting efficiency since the concentration of sensitizer on the electrode surface is limited.…”
Section: Solid-state Tta Upconversion Integrated Photovoltaicsmentioning
confidence: 99%
“…4 TTA-UC can be harnessed in a solar cell using either optically [5][6][7][8][9] or electronically coupled schemes. [10][11][12][13][14][15][16][17] The latter relies on incorporating sensitizer and annihilator molecules directly into the solar cell and has achieved photocurrent enhancements up to 0.315 mA cm À2 . 18 While a promising proof of concept, all electronically coupled TTA-UC solar cells to date absorb visible light (i.e., o700 nm).…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–5 ] TTA‐UC has gained great attention because it can proceed efficiently at low threshold intensities of incident incoherent light at or below 100 mW cm −2 . [ 1,6,7 ] This phenomenon was first discovered in single molecules of anthracene and phenanthrene as early as 1962, [ 8 ] continued research has produced increasingly efficient TTA‐UC systems and revealed the ease of tuning optical properties in multicomponent systems. [ 9–11 ] The first step in two‐component triplet upconversion is photon absorption by a sensitizer (donor) molecule, resulting in the generation of a singlet excited state, S 1 ( Figure a).…”
Section: Introductionmentioning
confidence: 99%